Security management of next generation telecommunications networks and services - Jacobs, Stuart; Wiley eBooks (Hoboken, New Jersey : IEEE Press Wiley, 2014)
"This book will cover network management security issues and currently available security mechanisms by discussing how network architectures have evolved into the contemporary NGNs which support converged services (voice, video, TV, interactive information exchange, and classic data communications). It will also analyze existing security standards and their applicability to securing network management. This book will review 21st century security concepts of authentication, authorization, confidentiality, integrity, nonrepudiation, vulnerabilities, threats, risks, and effective approaches to encryption and associated credentials management/control. The book will highlight deficiencies in existing protocols used for management and the transport of management information."--
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Computer networks -- Security measures; COMPUTERS -- Security -- Online Safety & Privacy; COMPUTERS -- Security -- Networking; COMPUTERS -- Security -- General; Computer networks -- Security measures; Electronic books